Rethinking Online Gaming: How Playing Intensity Predicts Social and Emotional Development in Elementary School Students - Zalfa Fitria Herayani; Sriyanto Sriyanto (Jurnal Ilmiah Sekolah Dasar, 2026)
The use of online games among elementary school children is increasing as digital technology advances. This phenomenon raises concerns about its impact on children's social and emotional development. This study aims to analyze the effect of online gaming intensity on social and emotional development, as well as the partial effect on emotional development via social development among elementary school students. This study uses a quantitative approach with a survey method and data collection using questionnaires, involving 250 students selected through proportional random sampling. The data in this study were analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM). The results showed that the intensity of online gaming had a positive but low effect on social development, suggesting a tendency toward social problems. The intensity of gaming also significantly affects emotional development, including increased anger and difficulty managing feelings. In addition, social development has a significant effect on emotional development and acts as a mediator. These findings emphasize the need for family and school guidance in the healthy use of online games.